THE IMPORTANCE OF ELECTRONIC LEARNING IN THE CONTINUOUS PROFESSIONAL DEVELOPMENT OF GENERAL EDUCATION SCHOOL TEACHERS - Akmal Shokhobiddinovich Nizamov (Journals Park Publishing, 2024)
The article discusses the importance of electronic learning in the system of continuous professional development (skill enhancement) of general education school teachers, the necessity of innovations in the system of professional development of personnel in the field, the concept of "lifelong learning," the "Continuous Professional Education" electronic platform, the prospects for the continuous professional development system of general education school teachers, and effective organization strategies for the educational process based on modern information technologies from a socio-pedagogical perspective.
Keywords: electronic platform, general education school teachers, continuous professional education, skill enhancement, concept, system.